2006
DOI: 10.4141/p05-242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leaf nitrogen concentration versus CND nutritional balance on shoot density and foliage colour of an established Kentucky bluegrass (Poa pratensis L.) turf

Abstract: N. 2006. Effects of leaf nitrogen concentration versus CND nutritional balance on shoot density and foliage colour of an established Kentucky bluegrass (Poa pratensis L.) turf. Can. J. Plant Sci. 86: 1107-1118. A 3-yr field study was conducted in a loam site and a sand site to determine the effects of N, P, and K application rates on N status, shoot density and foliage colour of Kentucky bluegrass clippings and to derive critical N values. The experiment was arranged in a completely randomized block design wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…This makes it difficult to make conclusive comparisons among studies that used different species and growing conditions. Our estimated sufficiency levels are within the few reported ranges for both the minimum and critical N concentrations (Bowman, 2003;Badra et al, 2006;Mangiafico and Guillard, 2007), but showed slight seasonal differences, as well as differences between the two cool-season turfgrass species.…”
Section: Defining Cool-season Turfgrass Sufficiency Levels For Nitrogsupporting
confidence: 81%
See 2 more Smart Citations
“…This makes it difficult to make conclusive comparisons among studies that used different species and growing conditions. Our estimated sufficiency levels are within the few reported ranges for both the minimum and critical N concentrations (Bowman, 2003;Badra et al, 2006;Mangiafico and Guillard, 2007), but showed slight seasonal differences, as well as differences between the two cool-season turfgrass species.…”
Section: Defining Cool-season Turfgrass Sufficiency Levels For Nitrogsupporting
confidence: 81%
“…A minimum concentration of N in the clippings, below which no net growth was predicted for this ryegrass species, was estimated to be 27 g kg -1 . Acceptable to optimum density and color of Kentucky bluegrass grown for sod in Quebec was obtained when clippings N concentrations ranged from 30.4 to ≥34.7 g kg -1 (Badra et al, 2006). In a field experiment in Connecticut with a mixed species cool-season lawn turf (Kentucky bluegrass, perennial ryegrass, and creeping red fescue [F. rubra subsp.…”
Section: Defining Sufficiency Levels Of Nitrogen In Cool-season Turfgmentioning
confidence: 99%
See 1 more Smart Citation
“…Dumort. ], 33 to 51 g kg -1 for perennial ryegrass, and 25 to 51 g kg -1 for Kentucky bluegrass (Mills & Jones, 1996), 27 to 35 g kg -1 for various species (Turner & Hummel, 1992), 30.4 to ≥ 34.7 g kg -1 for Kentucky bluegrass (Badra et al, 2006), 30 to 34 g N kg -1 for mixed species and separately for Kentucky bluegrass (Mangiafico & Guillard, 2007), and 32 to 46 g kg -1 and 28 to 42 g kg -1 for Kentucky bluegrass and tall fescue, respectively (Geng, Guillard, Mangiafico et al, 2014). These previous studies, however, report total N concentrations in the clippings and not the verdure.…”
Section: Fall Verdure Total N Concentrationsmentioning
confidence: 99%
“…Sufficiency or critical concentrations of total N in the clippings of various perennial cool‐season turfgrasses range from 24 to 82 g kg −1 , depending upon species and management systems (Badra et al., 2006; Butler & Hodges, 1967; Geng et al., 2014; Geng et al., 2014; Mangiafico & Guillard, 2007; Mills & Jones, 1996; Smith, Cornforth, & Henderson, 1985; Turner & Hummel, 1992). There are higher N concentrations in clippings than in the associated verdure (the aerial shoots and leaf blades remaining after mowing) (Kaufmann & Aldous, 1980; Picchioni & Quiroga‐Garza, 1999).…”
Section: Introductionmentioning
confidence: 99%